Protection from α-Synuclein induced dopaminergic neurodegeneration by overexpression of the mitochondrial import receptor TOM20 - Briana R. De Miranda (Nature Portfolio, 2020)
Abstract Dopaminergic neurons of the substantia nigra are selectively vulnerable to mitochondrial dysfunction, which is hypothesized to be an early and fundamental pathogenic mechanism in Parkinson’s disease (PD). Mitochondrial function depends on the successful import of nuclear-encoded proteins, many of which are transported through the TOM20–TOM22 outer mitochondrial membrane import receptor machinery. Recent data suggests that post-translational modifications of α-synuclein promote its interaction with TOM20 at the outer mitochondrial membrane and thereby inhibit normal protein import, leading to dysfunction, and death of dopaminergic neurons. As such, preservation of mitochondrial import in the face of α-synuclein accumulation might be a strategy to prevent dopaminergic neurodegeneration, however, this is difficult to assess using current in vivo models of PD. To this end, we established an exogenous co-expression system, utilizing AAV2 vectors to overexpress human α-synuclein and TOM20, individually or together, in the adult Lewis rat substantia nigra to assess whether TOM20 overexpression attenuates α-synuclein-induced dopaminergic neurodegeneration. Twelve weeks after viral injection, we observed that AAV2-TOM20 expression was sufficient to prevent loss of nigral dopaminergic neurons caused by AAV2-αSyn overexpression. The observed TOM20-mediated dopaminergic neuron preservation appeared to be due, in part, to the rescued expression (and presumed import) of nuclear-encoded mitochondrial electron transport chain proteins that were inhibited by α-synuclein overexpression. In addition, TOM20 overexpression rescued the expression of the chaperone protein GRP75/mtHSP70/mortalin, a stress-response protein involved in α-synuclein-induced injury. Collectively, these data indicate that TOM20 expression prevents α-synuclein-induced mitochondrial dysfunction, which is sufficient to rescue dopaminergic neurons in the adult rat brain.